Mensinergikan Nilai-Nilai Keagamaan Dengan Kearifan Lokal Sebagai Upaya Mewujudkan Masyarakat Madani (Studi Kasus Komunitas Keagamaan Kejawen di Desa Bajulan Kecamatan Loceret Kabupaten Nganjuk) - Siti Makhmudah (STAIFAS-Press, 2016)
This research executed in Countryside of Bajulan of Subdistrict Loceret of Regency Nganjuk. A lot of society assuming, that Countryside Bajulan very go together the mistical things like ritual-ritual kejawen that is nyadranan, clean countryside, ceremony of parna prahista, kirab pusoko and arca, ritual malem syuro, holy ritual water intake, ritual take a bath in source water, medium of lelaku ritual/meditating, ceremony of ngangsu kaweruh, and others. The Ritual-ritual not get out of the belief kejawen, like shalat at the same time sit, not execute the fasting ramadhan but following feast day of Ramadan and others Internal issue Formula this research is: 1) How form of activity of Islam kejawen and its resolving in in perpective of Islam in realizing and creating environment which madani in region Nganjuk 2) How method for the menyinergikan of religious value wisely is local budanya, in in perpective of Islam in realizing and creating environment which madani in region Nganjuk 3) How method applying for the menyinergikan of religious value wisely is local budanya, in in perpective of Islam in realizing and creating environment which madani in region Nganjuk? This research use the method qualitative (qualitative approach), in the form of utterance or article and behavior perceived the. Research type used is case study, that is a research conducted intensively, inch, and circumstantial to an organization, institute, or certain symptom. Procedure of data collecting with the interview, observation, and documentation. Analyse the data conducted by data discount, data presentation, and conclusion withdrawal. Checking of data Authenticity use the lengthening of taking part in, perception assidinity, and trianggulasi. Conclusion from this research result is: 1) forms of Activity of Islam kejawen in Countryside Bajulan among other things is nuptials, ceremony of tingkeban or mitoni, birth ceremony, ceremony of sunatan or circumcision, last offices, nyadran, clean of countryside, ceremony of commemoration of birthday of Prophet of Muhammad Saw., and ceremony of nifsu sya'ban of mid of month sya'ban (ruwah). 2) Method for the menyinergikan of religious value wisely is local culture in Countryside Bajulan is with the mission of bil matter, blaze the way the activity Islamic, Commemoration of Red-Letter Day Islam, Islam education, strategy infiltrate the culture, strategy of ta'lim or education, and sentimental strategy. 3) Method applying for the menyinergikan of religious value wisely local culture in perpective of religion in realizing and creating environment which madani in Countryside Bajulan by applying mission of bil matter, blaze the way the activity Islami, Commemoration of Red-Letter Day Islam, Islam education, forming of dirasah Islamiyah for the parent of, istighosah, and activity practice the shalat. With the the method applying, expected to make Islam as acceptable majority religion by society of Countryside Bajulan Â Keyword: Religious Values wisely is local, society madani